Factors affecting storage stability of various commercial phytase sources - Sulabo, R.C.; Jones, C.K.; Campbell, D.R.; Ratliff, B.W.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 360-d study was performed to evaluate the effects of environmental conditions on storage stability of exogenous phytases. Coated and uncoated products from 3 phytase sources (Ronozyme P, OptiPhos, and Phyzyme) were stored as pure forms, in a vitamin premix, or in a vitamin and trace mineral (VTM) premix. Pure products were stored at 0, 41, 73, and 99ºF (75% humidity). Premixes were stored at 73 and 99ºF. Sampling was performed on d 0, 30, 60, 90, 120, 180, 270, and 360. Sampling of the pure products stored at 0 and 41ºF was discontinued after d 120 due to mold growth in the 41ºF samples. Stability was measured as the residual phytase activity (% of initial) at each sampling point. For the stability of the pure forms, all interactive and main effects of phytase product, coating, time, and temperature of storage were significant (P < 0.01), except for time × coating interaction. When stored at 73ºF or less, pure phytases retained at least 91, 85, 78, and 71% of initial phytase activity at 30, 60, 90, and 120 d of storage, respectively. However, storing pure products at 99ºF reduced (P < 0.01) phytase stability, with OptiPhos retaining the most (P < 0.01) activity. Coating mitigated (P < 0.01) the negative effects of high storage temperature for Ronozyme and OptiPhos (from d 90 onward) but not for Phyzyme. For the stability of phytase in different forms of storage, all interactive and main effects of phytase product, form, coating, time, and temperature of storage were significant (P < 0.01). When stored at room temperature (73ºF), retained phytase activities for a majority of the phytase sources were more than 85, 73, and 60% of initial activity up to 180 d when stored as pure products, vitamin premixes, or VTM premixes, respectively. When stored at 99ºF, pure phytase products had greater (P < 0.01) retention of initial phytase activity than when phytases were mixed with the vitamin or VTM premixes. Coated phytases stored in any form had greater (P < 0.01) activity retention than the uncoated phytases at all sampling periods. In conclusion, storage stability of commercially available phytases is affected by duration of storage, temperature, product form, coating, and phytase source. Pure products held at 73ºF or less were the most stable. In premixes, longer storage time and higher temperature reduced phytase activity, but coating mitigated some of these negative effects.
Keywords: Swine; Enzyme; Phytase; Stability; Storage